2021
DOI: 10.14740/wjon1345
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Medicine in Oncology in the Developing World: Barriers and Concepts to Improve Status Quo

Abstract: Personalized medicine (PM) has revolutionized oncology management in high human development indexed countries. By interrogating both disease and host factors through a variety of tools, oncologists have been able to better target an individual's cancer, leading to improved outcomes. But both the tools used to define these variables, such as next generation sequencing, large immunohistochemical and fluorescence in situ hybridization (FISH) panels, and the weapons employed against each target are extremely expen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…Poor health in these countries is mainly due to inadequate prevention and lack of prudent access to basic health care. Moreover, since pooling of risk and insurance is not in place, it has led to health-related impoverishment [ 14 ]. Higher rates of cancer incidence significantly influence the health and finances of individuals and states.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Poor health in these countries is mainly due to inadequate prevention and lack of prudent access to basic health care. Moreover, since pooling of risk and insurance is not in place, it has led to health-related impoverishment [ 14 ]. Higher rates of cancer incidence significantly influence the health and finances of individuals and states.…”
Section: Resultsmentioning
confidence: 99%
“…There is a partially implemented health insurance policy that has several limitations, is not available to everyone, and also lacks funding. All of this leads to delays in presentation, diagnosis and treatment [ 14 ] ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Padala et al from the United States reviewed the epidemiology of renal cell carcinoma around the world [ 7 ]. Adeniji et al from Nigeria collaborated with colleagues from Nepal and the United States and reviewed the barriers and how to improve personalized medicine in oncology in the developing world [ 8 ]. Dulal et al from Nepal reported the feasibility of fewer fraction palliative radiotherapy in a resource-limited setting [ 9 ].…”
mentioning
confidence: 99%